1999
DOI: 10.1007/bf02462486
|View full text |Cite
|
Sign up to set email alerts
|

Visual evoked potentials induced by illusory outlines (Kanizsa's square)

Abstract: This report describes studies of visual evoked potentials (VEP) in ten subjects produced in response to Kanizsa's square and a control stimulus which did not involve a visual illusion but which had a similar spatial organization. The results showed that the amplitude-time characteristics of VEP depended on the illusory outlines. Differences in the parameters of VEP produced using the two stimuli were seen in the occipital, parietal, and temporal areas. VEP amplitude differences between the peaks of the N180 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2002
2002
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…This result indicates an earlier activation of visual cortex if compared to previous electrophysiological studies (i.e. 180-300 ms post-stimulus) [17,31,32] and it is consistent with neuroimaging data as far as neurotopographical localisation and perhaps timing of activation are concerned. Several fMRI, PET, rCBF and neurophysiological studies demonstrated an activation of extra-striate cortex (mainly V2, but also V3a, V4v, V7, V8) associated with illusory contours perception, both in humans and animals.…”
Section: 242supporting
confidence: 90%
See 2 more Smart Citations
“…This result indicates an earlier activation of visual cortex if compared to previous electrophysiological studies (i.e. 180-300 ms post-stimulus) [17,31,32] and it is consistent with neuroimaging data as far as neurotopographical localisation and perhaps timing of activation are concerned. Several fMRI, PET, rCBF and neurophysiological studies demonstrated an activation of extra-striate cortex (mainly V2, but also V3a, V4v, V7, V8) associated with illusory contours perception, both in humans and animals.…”
Section: 242supporting
confidence: 90%
“…The task consisted in a passive viewing paradigm; attention was focused on a central fixation point and not on the (possible) subjective figure, as in the present study. In another VEP study adopting a passive viewing task, Korshunova [17] recorded a peak-to-peak N180-P230 increase in amplitude at mesial occipital areas (O1 and O2 electrode sites) associated with illusory contour perception, along with asymmetric activation of the posterior temporal site (T5), probably near the extrastriate area (area 19).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The functional and neural bases of Kanizsa illusory contours have been investigated in normal human subjects by using evoked potentials [4,7,11], repetitive transcranial magnetic stimulation (rTMS) [2], functional magnetic resonance imaging (fMRI) [6,8 -10], and magnetoencephalography (MEG) [5]. Right occipital stimulation using rTMS significantly increased reaction times for illusory contour perception [2].…”
mentioning
confidence: 99%
“…Differences in VEPs related to visual illusory perception have been studied using the Kanizsa square [4,7,11] and the Poggendorff illusory figure [1]. Differences in VEPs produced in normal human subjects using the two stimuli, a Kanizsa square and a control stimulus, were seen in occipital, parietal, and temporal areas [4,7,11].…”
mentioning
confidence: 99%